A qualitative and quantitative analysis of radiation dose and image quality of computed tomography images using adaptive statistical iterative reconstruction. (8th May 2016) - Hussain, Fahad Ahmed; Mail, Noor; Shamy, Abdulrahman M.; Alghamdi, Suliman; Saoudi, Abdelhamid
Abstract : Image quality is a key issue in radiology, particularly in a clinical setting where it is important to achieve accurate diagnoses while minimizing radiation dose. Some computed tomography (CT) manufacturers have introduced algorithms that claim significant dose reduction. In this study, we assessed CT image quality produced by two reconstruction algorithms provided with GE Healthcare's Discovery 690 Elite positron emission tomography (PET) CT scanner. Image quality was measured for images obtained at various doses with both conventional filtered back‐projection (FBP) and adaptive statistical iterative reconstruction (ASIR) algorithms. A standard CT dose index (CTDI) phantom and a pencil ionization chamber were used to measure the CT dose at 120 kVp and an exposure of 260 mAs. Image quality was assessed using two phantoms. CT images of both phantoms were acquired at tube voltage (kV) of 120 with exposures ranging from 25 mAs to 400 mAs. Images were reconstructed using FBP and ASIR ranging from 10% to 100%, then analyzed for noise, low‐contrast detectability, contrast‐to‐noise ratio (CNR), and modulation transfer function (MTF). Noise was 4.6 HU in water phantom images acquired at 260 mAs/FBP 120 kV and 130 mAs/50% ASIR 120 kV. The large objects ( frequency < 7 lp / cm ) retained fairly acceptable image quality at 130 mAs/50% ASIR, compared to 260 mAs/FBP. The application of ASIR for small objects ( frequency > 7 lp / cm ) showed poor visibility compared to FBP at 260 mAs and even worse for images acquired at less than 130 mAs. ASIR blending more than 50% at low dose tends to reduce contrast of small objects ( frequency > 7 lp / cm ). We concluded that dose reduction and ASIR should be applied with close attention if the objects to be detected or diagnosed are small ( frequency > 7 lp / cm ). Further investigations are required to correlate the small objects ( frequency > 7 lp / cm ) to patient anatomy and clinical diagnosis. PACS number(s): 87.57.‐s, 87.57.C, 87.57.cf, 87.57.cj, 87.57.cm, 87.57.cp, 87.57.N, 87.57.nf, 87.57.np, 87.57.nt, 87.57.Q, 87.59.‐e, 87.59.B